2016
DOI: 10.1002/ajh.24429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with Hodgkin lymphoma with central nervous system involvement: An international multicenter collaboration

Abstract: Central nervous system (CNS) involvement is rare in patients with Hodgkin lymphoma (HL). Thus, the clinical features and outcomes are not well described. Cases of histologically confirmed CNS HL diagnosed between 1995 and 2015 were retrospectively identified in institutional (n 5 7), national (n 5 2), and cooperative group (n 5 1) databases. We screened 30,781 patients with HL in our combined databases and identified 21 patients meeting eligibility criteria, an estimated frequency of 0.07%. CNS involvement was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…CNS involvement in HL is extremely rare at diagnosis and in patients with relapsed or refractory disease. In a recent study, Cheah et al screened the clinical data of more than 30,000 HL patients and identified only 21 cases with CNS involvement, corresponding to an incidence <0.1% (3). Two retrospective series have reported a total of 37 HL patients with CNS involvement (2,3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNS involvement in HL is extremely rare at diagnosis and in patients with relapsed or refractory disease. In a recent study, Cheah et al screened the clinical data of more than 30,000 HL patients and identified only 21 cases with CNS involvement, corresponding to an incidence <0.1% (3). Two retrospective series have reported a total of 37 HL patients with CNS involvement (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Cheah et al screened the clinical data of more than 30,000 HL patients and identified only 21 cases with CNS involvement, corresponding to an incidence <0.1% (3). Two retrospective series have reported a total of 37 HL patients with CNS involvement (2,3). With the exception of one case of NLPHL who had CNS involvement at the time of the diagnosis, the other 36 cases were classical HL with roughly half of them presenting CNS involvement at the time of primary diagnosis, and the other half presenting CNS relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CNS involvement in Hodgkin lymphoma (HL) is 0.07% [1]. It can occur at the time of diagnosis or in the case of relapsed/refractory disease.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for the dissemination of HL into CNS are unknown due to the limited number of patients and heterogeneity of data. Various treatments were used in these patients, including surgical resection, corticosteroids, radiation, multiagent systemic chemotherapy, and autologous stem cell transplantation (ASCT) [1]. We report the case of a patient with refractory Hodgkin lymphoma with CNS involvement who achieved durable response with brentuximab vedotin-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation